SINERGI TNI ANGKATAN DARAT DENGAN PEMERINTAH DAERAH DALAM PENANGGULANGAN BENCANA ALAM - Agus Subagyo; Yudi Rusfiana (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT This paper would like to describe the synergy between the Army and the Government in the handling of natural disasters, by taking case study on the cooperation of Kodim 1611/Badung with Local Government of Badung Regency, both in the pre-disaster stage, during the disaster and after the disaster as for the research methods and approaches used is qualitative descriptive. Theories and concepts that are considered relevant to this research are related to disaster management and synergies. Based on the results of the research, it can be understood that the synergies held by Kodim 1611/Badung with Badung District Government are quite effective, although there are still obstacles in the handling of natural disasters, in the form of budget constraints, infrastructure, quality of personnel, sectoral ego between agencies, both parties, and low awareness of the community in the handling of natural disasters. Therefore, what should be done by both agencies is strengthening coordination, communication and collaboration on budget, means, personnel embodied in the MoU Keywords: synergy, army, government, natural disaster.